Barons, brokers, and buyers : the institutions and cultures of Philippine sugar - Billig, Michael S., 1956- (University of Hawai'i Press, 2003)
"This innovative ethnography takes a new approach to the study of Philippine sugar. Michael Billig examines sugar's decline within both the dynamic context of contemporary Philippine society and the global context of the international sugar market. His multi-sited ethnographic analysis focuses mainly on conflicts among the various elite sectors (planters, millers, traders, commercial buyers, politicians) and concludes that the most salient political, economic, and cultural trend in the Philippines today is the decline of rural, agrarian elite power and the rise of urban industrial, commercial, and financial power